2019
DOI: 10.7717/peerj.6450
|View full text |Cite
|
Sign up to set email alerts
|

Trends in fragmentation and connectivity of Paspalum quadrifarium grasslands in the Buenos Aires province, Argentina

Abstract: Background Despite its wide distribution worldwide, only 4.6% of temperate grasslands are included within systems of protected areas. In Argentina, this situation is even more alarming: only 1.05% is protected. The study area (central area of the southern Salado River basin) has a large extent of grasslands of Paspalum quadrifarium (Pq) which has been target since the middle of the last century of a variety of agricultural management practices including fire burning for cattle grazing. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 37 publications
0
6
0
4
Order By: Relevance
“…This decrease in annual productivity was strongly associated to natural or semi-natural grassland under cattle grazing, a region known as Flooding Pampa (Lara and Gandini, 2014). Despite the fact that natural or seminatural grassland is the main land cover in Flooding Pampa (Gandini et al, 2019), a noticeable increment of croplands during the last 20 years have been observed (Mestelan and Ramaglio, 2011;Rojas et al, 2011). This process was accompanied by an increment of livestock numbers that has doubled the historical values (Rojas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This decrease in annual productivity was strongly associated to natural or semi-natural grassland under cattle grazing, a region known as Flooding Pampa (Lara and Gandini, 2014). Despite the fact that natural or seminatural grassland is the main land cover in Flooding Pampa (Gandini et al, 2019), a noticeable increment of croplands during the last 20 years have been observed (Mestelan and Ramaglio, 2011;Rojas et al, 2011). This process was accompanied by an increment of livestock numbers that has doubled the historical values (Rojas et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the agriculture is based on a few crops: soybean and maize as summer crops, and wheat and barley as winter crops. Where the agriculture is not practicable, natural or semi-natural grassland under cattle grazing represents the main natural vegetation type (Lara and Gandini, 2014;Gandini et al, 2019).…”
Section: Study Areamentioning
confidence: 99%
“…Asimismo es probable que la distribución haya sido afectada por el factor antrópico. Sus poblaciones pueden haber disminuido al fragmentarse los pajonales de Paspalum quadrifarium (Gandini et al, 2019) con los que se encontraba asociada (Vervoorst, 1967), o por el contrario, su avance puede haberse facilitado por las rutas, caminos y vías de la red de ferrocarriles que actuarían como corredores biológicos, dado que se la ha encontrado en terraplenes (Vervoorst, 1967) y bordes de rutas.…”
Section: Discussionunclassified
“…These edaphic characteristics represent the main limiting factor for the development of agricultural activity. Therefore, areas of natural and semi‐natural grasslands predominate, constituting a floristic reservoir of the vegetation that dominated this landscape typically used as a source of forage for cattle (Gandini et al, 2019).…”
Section: Methodsmentioning
confidence: 99%